ANALISIS KARAKTERISTIK DAN KEBUTUHAN PARKIR DI UNIVERSITAS PENDIDIKAN NASIONAL - Dewa Ayu Putu Adhiya Garini Putri; Putu Budiarnaya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
The improvement of educational activities and facilities within a university makes the campus one of the potential areas that cause travel generation, which occurs at the National Education University. Parking irregularity is one of the problems during peak hours. This problem happens because there is no clear area, so vehicle owners can park their vehicles. In addition, there are no regulations stipulated in the arrangement of parking in the National Education Environment. Therefore it is necessary to research parking needs to be known at the Undiknas Campus, and spatial planning becomes more optimal. The study was conducted by cordon survey method, so the dimensions of the land available at the location and the number of vehicles entering and leaving the survey period can be accessed. Based on the analysis, the index parking of 2 wheelers (motorcycle) is 3.56 and 6.82 for 4 wheelers (car). This illustrates the parking space has exceeded its capacity. Parking shortage for 2 wheelers has amounted to 56.73% and 97.83% for 4-wheel vehicles. In 2030, the demand for parking space for two-wheeled vehicles is 3030 SRP with a standard plot plan of 0.75 x 2 m. As for the 4-wheeled vehicles, as many as 3463 parking space units with a standard plot plan is 3 x 5 m.